IFC Mobile Money Study 2011 : Sri Lanka - International Finance Corporation (Washington, DC, 2015)
Sri Lanka's population is still largely rural, nearly 85 percent lives outside of cities. There will probably be rural-to-urban migration in the future, which represents a potential opportunity to m-money providers. People working in cities often wish to repatriate their savings to their rural families conveniently and at a low cost. Income is fairly evenly spread across Sri Lanka s provinces, with the exception of the Western Province where Colombo, the largest city, is situated. Its GDP per capita places Sri Lanka near the average of comparable Southeast Asian countries. Malaysia is clearly an outlier with a considerably higher GDP per capita, but Sri Lanka s GDP is higher than that of the Philippines, where m-money has taken off dramatically. Poverty is less of a problem in Sri Lanka relative to countries like Bangladesh or Cambodia, where GDP per capita is much lower. The key point is that Sri Lanka is at a different stage in its economic development and is unlikely to have the same socioeconomic conditions that made m-money in Kenya accelerate so rapidly.